2000
DOI: 10.1034/j.1399-3011.2000.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective deuterium labeling of proRβ‐protons in the NMR structure determination of a helix‐turn‐helix turn peptide mimic

Abstract: The NMR structure of a small, side-chain-cyclized tripeptide mimic of the turn in the helix-turn-helix (HTH) motif was determined. The four beta-protons were stereospecifically assigned by stereoselective deuterium replacement of only the proR beta-protons. All 24 of 30 NOESY cross-peaks not involving chemically defined or freely rotating protons, and six of seven coupling constants from the P.COSY were used as distance and angle constraints in molecular modeling. MacroModel found 33/1000 structures in the NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The type II and II′ β-turns have sequence chiralities that make them particularly facile targets for de novo design . Etzkorn et al reported a peptidomimetic of the turn in the HTH motif of DNA-binding proteins. The conformational constraint in this system was achieved by an unusual linking of two amino acids with a side chain C–C bond and determined the structure.…”
Section: Introductionmentioning
confidence: 99%
“…The type II and II′ β-turns have sequence chiralities that make them particularly facile targets for de novo design . Etzkorn et al reported a peptidomimetic of the turn in the HTH motif of DNA-binding proteins. The conformational constraint in this system was achieved by an unusual linking of two amino acids with a side chain C–C bond and determined the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the cyclic peptide mimic with the hydroxamic acid functionality not only retained the hydrophobic property of the cyclic peptide mimic, but also introduced the linker and zinc-binding functional group into the targeted molecule 1 . The three-dimensional structure of the cyclic peptide mimic was determined by NMR in previous work . In the molecular modeling, the known 3-D structure of the cyclic peptide mimic 26 was attached to the linker and hydroxamic acid of SAHA from the cocrystal structure with the bacterial histone deacetylase-like protein (HDLP), which is similar to class I HDACs .…”
mentioning
confidence: 99%
“…Long coupling times using HATU or PyAOP produced no product. Steric hindrance was not a problem in previous cyclizations with Ala in the position of the α-aminosuberic acid . The instability of the hydroxamic acid functionality may have contributed to the low yield of 10 .…”
mentioning
confidence: 99%
See 2 more Smart Citations